PERANCANGAN SISTEM INFORMASI PEMESANAN PRODUK PERCETAKAN BERBASIS WEB PADA PT SULO DENGAN MENGGUNAKAN PENDEKATAN LINEAR SEQUENCE - Abdiel Bimasakti Elvis; Syafri Arief; Syaiful Rahman (KHARISMA Tech, 2018)
The purpose of this research is to build a Printing Product Order Information System that manages every customer ordering transaction and to generate a better ordering report. Stages in this study is divided into five stages, namely problem identification, data collection, system design, implementation, and system testing. System design includes system modeling that is done by using Data Flow Diagram and data modeling using ERD (Entity Relationship Diagram), then implemented using PHP and MySQL programming language as database and then testing on system using black box testing method. From the results of this penelilitan generated a web-based applications that can help the PT Sulo in handling consumer ordering transactions.